Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
ZenodoArchiveID: 4706000 previousDOI: 10.5281/zenodo.4706000 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3971656 10.5281/zenodo.4706000 10.53832/edtechhub.0029 2129771:YZIID28Y 2339240:7P4VDPLY 2339240:WYT4QCIW 2405685:85C5HVC7 2405685:I86XXKMH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH